2020 Bali's Coral Conservation: from pandemic challenge to Government coral garden project - Ida Bagus Agung Wicaksana (Bali Tourism Board, 2020)
Bali's coral reef restoration has been the topmost priority by the Indonesian Government and marine activists to save marine habitat in the long run. The action is necessary to halt severe damage that occurs in aquatic habitat over the years. The most apparent threat that has been faced is coral bleaching. Bali's water's tourism activities have sharply dipped between early to mid-2020, yet it did not stop the coral bleaching phenomenon. The phenomenon is occurring due to water temperature rise. The Government's decision to restrict public activity made the conservation task impossible to be done. Albeit challenges in coral conservation became a daunting task in 2020, pleasant news also came from the central Government. Coordinating Minister for Maritime Affairs and Investment Luhut Binsar Pandjaitan revealed the central Government had compiled a National Economic Recovery (PEN) program for Indonesia Coral Reef Garden (ICRG) Bali. The program is coral reef restoration activities centered in Nusa Dua and several other areas such as Sanur, Serangan, Pandawa Beach, and Buleleng. The coral reef garden will be built using the Ministry of Marine Affairs and Fisheries National Economic Recovery fund worth IDR 111.2 billion. The fund will be used to build a 50 hectares coral plantation. Meanwhile, the Governor of Bali, I Wayan Koster, expressed his appreciation toward the program. Koster believed the program would significantly impact the community, especially in supporting economic recovery since the national economic recovery activities will involve more than 11,000 workers.